Selection of Normative Group Affects Rates of Mild Cognitive Impairment in Parkinson's Disease. Issue 5 (14th February 2018) - Wyman‐Chick, Kathryn A.; Martin, Phillip K.; Weintraub, Daniel; Sperling, Scott A.; Erickson, Lauren O.; Manning, Carol A.; Barrett, Matthew J.
ABSTRACT: Objective : The objective of this study was to examine the impact of different methods of standardizing cognitive data in the Parkinson's Progression Marker Initiative. Methods: Cognitive data from 423 participants with Parkinson's disease were included (age = 61.7 [9.7], education = 15.6 [3.0]). Internal norms were calculated using the group mean and standard deviation of the healthy control group. Published norms were compared to the overall group mean of and to age‐stratified norms from healthy controls for each neuropsychological test over 4 visits. Rates of mild cognitive impairment were calculated using established criteria. Results: The use of internal norms resulted in lower standardized scores than published norms on all tests with the exception of memory and processing speed ( P  ≤ .001). Individuals were 1.5 to 2.1 times more likely to be diagnosed with mild cognitive impairment using internal norms than published norms. Conclusions: Standardization approaches with cognitive data are not interchangeable. Selection of a normative comparison group impacts research and clinical interpretations of cognitive data. © 2018 International Parkinson and Movement Disorder Society